THE EFFECT OF HMB SUPPLEMENTATION ON MUSCLE RECOVERY AND HYPERTROPHY IN STRENGTH-TRAINED ATHLETES: A LITERATURE REVIEW - Siedlecki, Rafał; Góral, Marta; Fidorowicz, Dominik; Sagan, Daniel; Sergiel, Katarzyna Helena; Torbacka, Emilia; Skuza, Aleksandra Irena; Downar-Zapolska, Magda; Mikłaszewicz, Agnieszka; Bednarczuk, Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Background: Post-exercise recovery and effective stimulation of muscle hypertrophy are essential for high performance in strength and strength-endurance sports. Intensive resistance training causes muscle microdamage, metabolic stress, and inflammation, confirming the importance of recovery for adaptation. β-hydroxy-β-methylbutyrate (HMB), a leucine metabolite, has been studied for its possible anti-catabolic and anabolic potential.Aim: This review evaluates current evidence on HMB supplementation, focusing on muscle recovery, hypertrophy, supplement forms, and athlete populations, with attention to practical uses and research limitations.Methodology: A narrative literature review was conducted based on searches in PubMed, Scopus, and Web of Science for studies published between 2015 and 2025. Search terms included “HMB,” “β-hydroxy-β-methylbutyrate,” “muscle recovery,” “hypertrophy,” “resistance training,” “Ca-HMB,” and “HMB-FA.” Only English-language studies involving human participants and reporting outcomes related to muscle recovery, hypertrophy, or strength were included. Data extracted included participant characteristics, HMB form and dosage, supplementation duration, training protocol, and outcomes such as muscle soreness, strength, and biomarkers of muscle damage. Results were synthesized descriptively, with comparisons based on supplement form, training status, and study quality.Results and Discussion: HMB is endogenously produced in small amounts and is supplemented exogenously as calcium salt (Ca-HMB) or free acid (HMB-FA). Research suggests that HMB reduces muscle-damage biomarkers, supports membrane stability, modulates protein metabolism, and may enhance satellite cell activity. HMB can accelerate recovery, reduce delayed onset muscle soreness (DOMS), and promote hypertrophy, especially in novice or returning athletes. Effects vary by dosage, supplementation duration, form, and individual training status. Evidence indicates greater benefits in early adaptation phases, during high training loads, or during periods of increased risk of muscle loss.Conclusions: HMB supplementation appears to be beneficial under specific conditions for supporting muscle recovery and hypertrophy. It may accelerate functional restoration, reduce muscle damage, and support fiber remodeling. Benefits are most pronounced in less-trained athletes, individuals returning from breaks, or during high training loads. Effectiveness depends on supplement form, dosage, and individual physiology. HMB is safe and well-tolerated, though additional research is needed to standardize protocols, compare Ca-HMB and HMB-FA, and assess long-term effects across athlete populations.